2008
DOI: 10.1002/chem.200800281
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling the Alkyne Prins Cyclization: The Stability of Dihydropyranyl Cations

Abstract: The relative stability of the intermediates involved in the alkyne Prins cyclization and the competitive 2-oxonia-[3,3]-sigmatropic rearrangement was studied. This rearrangement was shown to occur slowly under typical alkyne Prins cyclization conditions when the allenyl oxocarbenium ion that results from the rearrangement is similar to or higher in energy than the starting alkynyl oxocarbenium ion. The formal 2-oxonia-[3,3]-sigmatropic rearrangement may be disfavored by destabilizing the resultant allenyl oxoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…This is a mechanism typical of the Prins-type cyclization reactions. [44][45][46][47][48][49] The transition state of this process (11-TS1) clearly reveals a new s bond formed between C1-C2 (see Fig. 2 and Table 2), but the distances at C3-C4 and C3-C5 (3.60Å and 3.65Å) are, in contrast to the case of 10, beyond the van der Waals contact and hence indicate little covalent interactions.…”
Section: Dft Studies Of the Intramolecular Alkyne-dithiolium Cycloaddmentioning
confidence: 93%
See 1 more Smart Citation
“…This is a mechanism typical of the Prins-type cyclization reactions. [44][45][46][47][48][49] The transition state of this process (11-TS1) clearly reveals a new s bond formed between C1-C2 (see Fig. 2 and Table 2), but the distances at C3-C4 and C3-C5 (3.60Å and 3.65Å) are, in contrast to the case of 10, beyond the van der Waals contact and hence indicate little covalent interactions.…”
Section: Dft Studies Of the Intramolecular Alkyne-dithiolium Cycloaddmentioning
confidence: 93%
“…The rst reaction pathway is a concerted 1,3-dipolar cycloaddition 39,40 that directly leads to a cage-shaped intermediate IM-3 with the backbones of B and C rings assembled simultaneously. The second one is a stepwise pathway, in which the alkynyl group attacks the carbocation of dithiolium ring via an alkyne Prinstype cyclization [44][45][46][47][48][49] at rst. The electrophilic cyclization occurs with a 5-exo-dig regioselectivity, forming the B ring only.…”
Section: Introductionmentioning
confidence: 99%
“…Other Lewis acids, for example, AlCl 3 , FeBr 3 , FeCl 2 , TMSCl, and InCl 3 were also screened. Among them, only AlCl 3 and FeBr 3 gave low conversions to the cyclized product 2 a and the corresponding brominated bridged bicyclic enamine, respectively ( 13). Moreover, when the five-membered ring analogue 3 a was treated with 6 M aq HCl (9 equiv.…”
Section: Tionmentioning
confidence: 99%
“…A formal alkyne aza-Prins cyclization reaction path [13] is suggested for the formation of cyclobutenamine 10 a (Scheme 4). An N-to-C propargyl shift of 9 a with FeBr 3 leads to ketenimine 11.…”
Section: Tionmentioning
confidence: 99%
“…The calculations also showed that the trimethylsilyl group does not have a direct effect on the formally positively charged carbon atom. 84 To confirm that no racemization occurred during the cyclizations to the tetrasubstituted dihydropyrans, we treated alcohol (R)-134 with phenylacetaldehyde and iron(III) chloride. The resulting dihydropyran 135 showed a slightly reduced but still synthetically useful enantiomeric purity compared with the starting homopropargylic alcohol (R)-134 (Scheme 48).…”
mentioning
confidence: 99%